Strategic Foresight Capability, Dynamic Capabilities, Organizational Resilience, Innovation Speed, and Firm Performance: Testing a Structural Equation Model - Nowak, Katarzyna; McKenzie, Oliver; Papadakis, Dimitrios (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The purpose of this study was to examine the direct and indirect relationships among strategic foresight capability, dynamic capabilities, organizational resilience, innovation speed, and firm performance through a comprehensive structural equation model among organizations operating in Canada.Methods and Materials: This study employed a quantitative, cross-sectional design using structural equation modeling (SEM). The research population consisted of managers, executives, innovation specialists, and strategic planning professionals employed in medium-sized and large organizations across Canada. Using a stratified random sampling approach, data were collected from 542 participants representing manufacturing, technology, financial services, healthcare, logistics, and professional service sectors. Data were gathered using standardized instruments measuring strategic foresight capability, dynamic capabilities, organizational resilience, innovation speed, and firm performance. The psychometric properties of the instruments were evaluated through confirmatory factor analysis, composite reliability, and convergent validity assessments. Data analysis was conducted using SPSS 29 and AMOS 29. The measurement and structural models were assessed using maximum likelihood estimation, bootstrap procedures, and multiple model-fit indices, including χ²/df, CFI, TLI, IFI, GFI, RMSEA, and SRMR.Findings: The measurement model demonstrated excellent fit to the data (χ²/df = 2.31, CFI = .957, TLI = .952, IFI = .957, GFI = .924, RMSEA = .049, SRMR = .041). Structural equation modeling revealed that strategic foresight capability positively influenced dynamic capabilities (β = .73, p < .001), organizational resilience (β = .41, p < .001), and firm performance (β = .18, p < .001). Dynamic capabilities significantly affected organizational resilience (β = .48, p < .001) and innovation speed (β = .56, p < .001). Organizational resilience exerted a positive effect on innovation speed (β = .29, p < .001), while innovation speed emerged as the strongest predictor of firm performance (β = .61, p < .001). The model explained 61% of the variance in dynamic capabilities, 67% of the variance in organizational resilience, 71% of the variance in innovation speed, and 74% of the variance in firm performance. Bootstrap analyses further confirmed significant indirect effects, indicating that dynamic capabilities, organizational resilience, and innovation speed jointly mediated the relationship between strategic foresight capability and firm performance.Conclusion: The findings demonstrate that strategic foresight capability serves as a foundational organizational capability that enhances firm performance through the development of dynamic capabilities, organizational resilience, and innovation speed. Organizations that systematically anticipate future developments, adapt resources effectively, maintain resilience under uncertainty, and accelerate innovation processes are more likely to achieve superior performance outcomes. The study contributes to strategic management literature by providing empirical evidence for an integrated capability-based model of organizational success in dynamic and uncertain environments.